Web content-based image retrieval system based on 4-D structural features - Tushnytskyy, Ruslan; Perevalova, Inna; Pavlyuk, Galyna (Видавництво Львівської політехніки, 2010)
An approach to search images from a databases by structural features got from the three stages clustering algorithm is considered. Software packages architecture for visual pattern processing is presented.
Keywords: clustering; content-based image retrieval; structural properties; visual pattern